Vascular Endothelial Cells and Innate Immunity. Issue 6 (June 2020) - Shao, Ying; Saredy, Jason; Yang, William Y.; Sun, Yu; Lu, Yifan; Saaoud, Fatma; Drummer, Charles; Johnson, Candice; Xu, Keman; Jiang, Xiaohua; Wang, Hong; Yang, Xiaofeng
Abstract : In addition to the roles of endothelial cells (ECs) in physiological processes, ECs actively participate in both innate and adaptive immune responses. We previously reported that, in comparison to macrophages, a prototypic innate immune cell type, ECs have many innate immune functions that macrophages carry out, including cytokine secretion, phagocytic function, antigen presentation, pathogen-associated molecular patterns-, and danger-associated molecular patterns-sensing, proinflammatory, immune-enhancing, anti-inflammatory, immunosuppression, migration, heterogeneity, and plasticity. In this highlight, we introduce recent advances published in both ATVB and many other journals: (1) several significant characters classify ECs as novel immune cells not only in infections and allograft transplantation but also in metabolic diseases; (2) several new receptor systems including conditional danger-associated molecular pattern receptors, nonpattern receptors, and homeostasis associated molecular patterns receptors contribute to innate immune functions of ECs; (3) immunometabolism and innate immune memory determine the innate immune functions of ECs; (4) a great induction of the immune checkpoint receptors in ECs during inflammations suggests the immune tolerogenic functions of ECs; and (5) association of immune checkpoint inhibitors with cardiovascular adverse events and cardio-oncology indicates the potential contributions of ECs as innate immune cells.